2020
DOI: 10.3390/ijms21186894
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Exosomes as a Therapy for Stroke Recovery

Abstract: Stroke is the leading cause of disability, and stroke survivors suffer from long-term sequelae even after receiving recombinant tissue plasminogen activator therapy and endovascular intracranial thrombectomy. Increasing evidence suggests that exosomes, nano-sized extracellular membrane vesicles, enhance neurogenesis, angiogenesis, and axonal outgrowth, all the while suppressing inflammatory reactions, thereby enhancing functional recovery after stroke. A systematic literature review to study the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Secondly, the risk of vascular occlusion and microvascular thrombosis is reduced after transplantation, and MSC-EVs do not have the potential of tumor transformation because they cannot self-replicate. Third, MSC-EV has a robust structure and can be stored at -80°for a long time without loss of biological activity [198]. Finally, intravenous injection of MSC-EVs can reduce the peripheral immunosuppression (i.e., the decrease of B cells, NK cells, and T cells) after IS [95].…”
Section: Gene Transfection or Overexpressionmentioning
confidence: 99%
“…Secondly, the risk of vascular occlusion and microvascular thrombosis is reduced after transplantation, and MSC-EVs do not have the potential of tumor transformation because they cannot self-replicate. Third, MSC-EV has a robust structure and can be stored at -80°for a long time without loss of biological activity [198]. Finally, intravenous injection of MSC-EVs can reduce the peripheral immunosuppression (i.e., the decrease of B cells, NK cells, and T cells) after IS [95].…”
Section: Gene Transfection or Overexpressionmentioning
confidence: 99%
“…Activation of CD4 and CD6 T lymphocytes and the decrease of the decline in dendritic cells can be intensified by MSC exosomes. [ 23 ] In animal studies, the increase in oligodendrogenesis-associated markers (2′, 3′-cyclic-nucleotide 3′-phosphodiesterase [CNPase], A2B5, and myelin oligodendrocyte glycoprotein) are associated with the white matter repair. [ 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes mellitus leads to vascular endothelial cell dysfunction and exuberant angiogenesis, but it is also conducive to dysfunctional neovascularization and poor recovery in ischemic stroke. EPCs can contribute to vascular endothelial repair and angiogenesis ( 34 ); increasing angiogenesis is associated with neurological functional outcome after stroke ( 35 ). Our in vivo study indicated that LV-APN-EPCs treatment had effects on the recovery of neurological functional deficits in diabetic stroke rats, but EPC transplantation alone had little effect.…”
Section: Discussionmentioning
confidence: 99%